Postoperative Renal Outcomes of Patients Receiving Percutaneous Nephrolithotomy versus Pyelolithotomy: A Population-Based Cohort Study. (2nd May 2018) - Chen, Fang-Ting; Liu, Fu-Chao; Cheng, Chih-Wen; Lin, Jr-Rung; Yu, Huang-Ping
Abstract : The aim of this population-based cohort study was to explore postoperative renal outcomes of patients receiving pyelolithotomy versus percutaneous nephrolithotomy (PCNL). Data were retrieved from the Taiwan National Health Insurance Research Database. During the period from Jan 1, 1998, to Dec 31, 2012, there were 2549 and 21654 patients who underwent pyelolithotomy and PCNL, respectively. The postoperative incidence of new diagnosed end stage renal disease (ESRD) was statistically analyzed and compared between the pyelolithotomy and PCNL groups. The perioperative complications of two groups were also analyzed. In comparison to pyelolithotomy, PCNL achieved lower new diagnosed ESRD (1.38% versus 2.28%, p = 0.0004 ). Patients receiving PCNL had significantly higher rates of preoperative hypertension, diabetes mellitus, pulmonary disease, cerebrovascular disease, and coronary artery disease. The hospital stay was shorter in PCNL groups compared with pyelolithotomy groups (8.31 days versus 12.59 days, p = 0.0006 ). In conclusion, PCNL contributed to lower rates of new diagnosed ESRD and hospital stay when compared to pyelolithotomy.